Study on seismic performance of suspended ceiling system with semi-free boundary condition. (15th January 2023) - Wang, Yong; Jiang, Huanjun; Motoyui, Shojiro; Kasai, Kazuhiko; Qin, Zhiyuan; Huang, Youlu
Highlights: A new boundary condition, i.e. semi-free condition, is proposed for suspended ceiling system. The first large-scale shaking table test on double-layer suspended ceiling system wildly applied in China is conducted. Working mechanism and seismic performance of suspended ceiling system with semi-free boundary condition are investigated. The damage to the ceiling perimeter is prevented by the developed boundary condition. A simplified numerical model for suspended ceiling with semi-free boundary condition is developed and verified. Abstract: The failure of suspended ceiling system (SCS) has been one of the most widely reported seismic damage to non-structural components in buildings in recent years. In China, there are several types of SCSs applied in practice, among which the double-layer SCS with mineral wool boards is widely used in public buildings. It was found from the past earthquakes that the ceiling perimeter is one of the most vulnerable parts of SCS due to lack of reliable connection at the boundary. In this study a new semi-free boundary condition is proposed to improve the seismic performance of SCS. The full-scale shaking table tests on this type of SCS installed on a steel platform are conducted. The working mechanism, failure patterns, damage evolution, and earthquake responses including acceleration, displacement, and strain responses are studied. Experimental results verify that the proposed boundary condition is able to protect the ceiling perimeter from damage. The failure of SCS is mainly caused by the high vulnerability of grid connections. The pounding at the perimeter of SCS affects the seismic performance of the SCS harmfully. Effective seismic measures should be developed to reduce the impact between the ceiling and surroundings. A simplified numerical model for SCS with semi-free boundary condition is developed using OpenSEES. The calculated acceleration and displacement responses agree well with the test results. Moreover, seismic design recommendations for the type of SCS are provided.